An External Independent Validation of APACHE IV in a Malaysian Intensive Care Unit - Wong, R.S.; Ismail, N.A.; Tan, C.C. (Annals of the Academy of Medicine, Singapore, 2015)
INTRODUCTION: Intensive care unit (ICU) prognostic models are predominantly used in more developed nations such as the United States, Europe and Australia. These are not that popular in Southeast Asian countries due to costs and technology considerations. The purpose of this study is to evaluate the suitability of the acute physiology and chronic health evaluation (APACHE) IV model in a single centre Malaysian ICU.